1996
DOI: 10.1053/jhep.1996.v24.pm0008707286
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of the protein kinase substrate annexin in human hepatocellular carcinoma

Abstract: Annexin (AX) constitutes a new family of Ca2+-dependent membrane-binding proteins; 13 of them have been described. Among these, annexin-1 (AX-I) has displayed many biological functions in vitro. Its actual role in vivo, however, remains unknown. We already reported that AX-I was expressed in proliferating (regenerating) hepatocytes at both protein and messenger RNA (mRNA) levels. The role of AX-I in human hepatocellular carcinoma (HCC) remains obscure. In this study, the amounts of AX-I at protein and mRNA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 57 publications
4
65
0
Order By: Relevance
“…In contrast to the suppressed expression of ANXA1 observed in the above-mentioned cancers, increased ANXA1 expression has been reported in pancreatic (Bai et al, 2004), hepatic (Masaki et al, 1996), glial (Johnson et al, 1989) and stomach cancers (Sinha et al, 1998), suggesting that the functional role of ANXA1 may be tissue-and cell type-specific. These findings further highlight the complexity and highly specific nature of ANXA1 physiological functions.…”
Section: Introductionmentioning
confidence: 79%
“…In contrast to the suppressed expression of ANXA1 observed in the above-mentioned cancers, increased ANXA1 expression has been reported in pancreatic (Bai et al, 2004), hepatic (Masaki et al, 1996), glial (Johnson et al, 1989) and stomach cancers (Sinha et al, 1998), suggesting that the functional role of ANXA1 may be tissue-and cell type-specific. These findings further highlight the complexity and highly specific nature of ANXA1 physiological functions.…”
Section: Introductionmentioning
confidence: 79%
“…56 Immunohistochemical studies of breast and hepatocellular carcinoma also indicated that AnxI is associated with tumor progression. [57][58][59] The contribution of AnxI to pseudopodial extension during migration may explain AnxI's association with tumor progression and HGF signaling seen in other cells 18 and with activated HGF in U87 pseudopodia. Also, AnxII was previously identified more frequently in high-grade than low-grade gliomas, 50 of 65 and three of 10 tumors, respectively, following 2D electrophoresis of tissue samples.…”
mentioning
confidence: 99%
“…While we were carrying these experiments, ANX1 was reported to be strongly expressed in human hepatocellular (hcc) carcinoma cells, suggesting that its induction in the liver could be associated with malignant transformation. 4,5 We therefore addressed the question of the role of ANX1 in liver transformation.Recently, transgenic mice (ASV) expressing the SV40 early region coding for large T antigen under the control of the liver-specific human antithrombin III gene promoter have been created in our laboratory to study oncogenic transformation on hepatocyte function. 6 Phenotypically, the animals present a hepatocellular carcinoma, with a neoplasia at 3 to 9 weeks and later (after tumor development) a severe dysplasia, an augmentation of hepatocytes in S phases, an important cytolysis (necrosis), and an early apoptosis (2.5%-5%).…”
mentioning
confidence: 99%
“…While we were carrying these experiments, ANX1 was reported to be strongly expressed in human hepatocellular (hcc) carcinoma cells, suggesting that its induction in the liver could be associated with malignant transformation. 4,5 We therefore addressed the question of the role of ANX1 in liver transformation.…”
mentioning
confidence: 99%